AKTIVITAS KOMUNIKASI DALAM RITUAL KEAGAMAAN - Muhammad Najmuddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
Tolotang community communication activities include communicative situations, communicative events and communicative acts. Communicative situation or the context of the occurrence of communication is an atmosphere that describes the events or communication processes in a series of religious ritual activities of the Tolotang community, among others: Bulu Lowa, Amparita Market and Perrinyameng. Communicative events are events that illustrate the belief system in the religious rituals of the Tolotang community including: Mappaenre Inanre, Inanrē, Sipulung, Tudang sipulung, Iēnrēkeng. The Tolotang community also believes in the revelation system as a communicative act